Seasonal recurrence and modular assembly of an Arctic pelagic marine microbiome - Priest, Taylor; Oldenburg, Ellen; Popa, Ovidiu; Dede, Bledina; Metfies, Katja; von Appen, Wilken-Jon; Torres-Valdés, Sinhué; Bienhold, Christina; Fuchs, Bernhard M.; Amann, Rudolf; Boetius, Antje; Wietz, Matthias (Nature communications, 2025)
Deciphering how microbial communities are shaped by environmental variability is fundamental for understanding the structure and function of ocean ecosystems. While seasonal environmental gradients have been shown to structure the taxonomic dynamics of microbiomes over time, little is known about their impact on functional dynamics and the coupling between taxonomy and function. Here, we demonstrate annually recurrent, seasonal structuring of taxonomic and functional dynamics in a pelagic Arctic Ocean microbiome by combining autonomous samplers and in situ sensors with long-read metagenomics and SSU ribosomal metabarcoding. Specifically, we identified five temporal microbiome modules whose succession within each annual cycle represents a transition across different ecological states. For instance, Cand . Nitrosopumilus, Syndiniales, and the machinery to oxidise ammonia and reduce nitrite are signatures of early polar night, while late summer is characterised by Amylibacter and sulfur compound metabolism. Leveraging metatranscriptomes from Tara Oceans , we also demonstrate the consistency in functional dynamics across the wider Arctic Ocean during similar temporal periods. Furthermore, the structuring of genetic diversity within functions over time indicates that environmental selection pressure acts heterogeneously on microbiomes across seasons. By integrating taxonomic, functional and environmental information, our study provides fundamental insights into how microbiomes are structured under pronounced seasonal changes in understudied, yet rapidly changing polar marine ecosystems. Microbial communities are shaped by their environment. Here, the authors demonstrate temporal structuring of microbial communities in the pelagic Arctic Ocean, using remote, long-term sampling with long-read metagenomics and SSU ribosomal metabarcoding.